Promoting Finnwool with Green Production and Sustainability: Aspects from the Past to the Future, from Crafts to Industry. (3rd July 2019) - RÄisÄnen, Riikka
Abstract: This paper aims to discover ways to promote a native sheep breed in Finland, the Finnsheep. The focus is placed on wool, its characteristics and applications. In history, the sheep was an essential animal for families because it provided textile materials and meat. Over the decades, the population of Finnsheep has declined. The paper reviews articles ( N = 169) in newspapers and magazines from 1915 to 2015. Data-based qualitative content analysis was used. The analysis shows that, in spite of numerous projects and much education, little progress has been made to increase the farming and large-scale utilization of Finnwool. The amounts of pure Finnwool are small and insufficient in themselves for industrial-scale spinning. Also, the quality of wool sent from farms to spinning mills varies greatly. The low price of wool hinders farmers' interest in paying attention to quality. The main focus is meat production. Trends such as green consumption, a slow lifestyle, local production and services, and support for biological and cultural diversity could positively influence the demand for Finnsheep. For this, cooperation is needed between different actors. High quality and novel design in the products and services related to Finnsheep are key factors for promotion.